1997
DOI: 10.5636/jgg.49.1267
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Self-Potential Profiling of Izu-Oshima Volcano, Japan

Abstract: , annual self-potential (SP) surveys were carried out on Izu-Oshima, a small volcanic island. A terrain-related SP distribution of about -1 mV per meter of elevation was observed outside the caldera in all five surveys. Inside the caldera, SP increases from about -350 mV to near 0 mV (relative to the coastline) as the summit crater is approached, although negative anomalies of small spatial extent are manifest. Selfpotential inside the caldera decreased by about 100 mV between the March 1989 and the March 1990… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 11 publications
4
31
0
Order By: Relevance
“…are homogeneous (Ishido, 1989). Ishido et al (1997) showed by a numerical simulation that relatively high SP appeared around the summit on a volcano with a deeper water table beneath the summit area than beneath the flank. The assumption of the linear topographic effect will not be valid if meteoric water downflows at the summit area are suppressed by intense upflows of high temperature volcanic gases as also shown by Ishido et al (1997).…”
Section: A Model For the Positive Sp Anomalymentioning
confidence: 99%
See 1 more Smart Citation
“…are homogeneous (Ishido, 1989). Ishido et al (1997) showed by a numerical simulation that relatively high SP appeared around the summit on a volcano with a deeper water table beneath the summit area than beneath the flank. The assumption of the linear topographic effect will not be valid if meteoric water downflows at the summit area are suppressed by intense upflows of high temperature volcanic gases as also shown by Ishido et al (1997).…”
Section: A Model For the Positive Sp Anomalymentioning
confidence: 99%
“…However, the parameter A was searched together with B under the assumption that the linear topographic effect holds even around the summit area, so that the A parameter and the consequent current strength would be overestimated. Ishido et al (1997) performed numerical simulations of the hydrothermal convection before and after a magma intrusion into shallow part of a volcano to interpret the stable positive sense SP anomaly centered over the active vent of Izu-Oshima volcano, Japan. Based on their results, ascent of high temperature volcanic gases above the magma suppressed meteoric water downflows and resulted in the relatively high potential around the summit crater.…”
Section: A Model For the Positive Sp Anomalymentioning
confidence: 99%
“…Corwin and Hoover, 1979;Ishido et al, 1989;Lénat, 1995;Ishido et al, 1997;Yasukawa et al, 2005). Self-potential anomalies are caused by differences in temperature, electrical resistivity or moisture content, as well as fluid flow in response to pressure gradients.…”
Section: Methodsmentioning
confidence: 98%
“…Indeed, while streaming potentials were known to contribute to the static self-potential (SP) distribution in geothermal areas and active volcanoes (e.g., CORWIN and HOOVER, 1979;ISHIDO et al, 1997;YASUKAWA et al 2003;REVIL et al 2003), recent experiments have demonstrated that time variations of SP can be unambiguously identified and associated with time-varying fluid flow in geophysical systems from metric to kilometric scales GENSANE et al, 1999;PERRIER et al, 1999PERRIER et al, , 2002aDOUSSAN et al, 2002;TRIQUE et al, 2002;REVIL et al, 2002). These developments revived the exciting possibility of using long-term SP monitoring to anticipate volcanic eruptions or earthquakes (e.g., ZLOTNICKI et al, 2001;MIZUTANI et al, 1976;PARK et al, 1993;TRIQUE et al, 1999).…”
Section: Introductionmentioning
confidence: 99%